Measurement of Flow-Mediated Vasodilatation: A Lesson From the FMDJ Study - Tomiyama, Hirofumi; Saisu, Tomoko; Yamashina, Akira (International Heart Journal, 2017)
The FMDJ study, a multicenter prospective observational study conducted in Japan, demonstrated the acceptable reliability of measurement of flow-mediated vasodilatation (FMD) using a semi-automatic device in individual institutions. However, in about 10% of Japanese subjects, adequate scans to determine the brachial arterial diameter failed to be obtained. The prevalence of inadequate scans was higher in women than in men, while obesity had no influence on the inadequate scan rate. The FMDJ study also proposed that attending periodic refresher courses on the measurement of FMD is needed for maintaining competency. Finally, the FMDJ study proposed reference values for FMD. Thus, FMD measurement may be categorized as a clinically applicable tool on the basis of class IIb (exploratory cohort study with good reference standards) evidence.